2005
DOI: 10.1192/bjp.187.6.516
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive heterogeneity in first-episode schizophrenia

Abstract: At illness onset, cognitive heterogeneity is present in people with schizophrenia, with a high proportion having undergone general cognitive decline. However, working memory impairment may be a common feature. Lower premorbid IQ is a risk factor for an earlier onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
86
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 53 publications
(64 reference statements)
21
86
0
5
Order By: Relevance
“…As expected, in healthy controls, premorbid IQ estimated by the NART is usually very similar to current IQ (e.g. Joyce et al, 2005) as measured by tests such as the Wechsler Adult Intelligence Scale -Revised (WAIS-R; Wechsler, 1981), supporting the validity of the NART. The NART also probably gives a valid measure of premorbid IQ in most people with schizophrenia (Frith et al, 1991;Crawford et al, 1992).…”
Section: Simultaneous Estimate Of Premorbid and Current Intellectual mentioning
confidence: 77%
See 1 more Smart Citation
“…As expected, in healthy controls, premorbid IQ estimated by the NART is usually very similar to current IQ (e.g. Joyce et al, 2005) as measured by tests such as the Wechsler Adult Intelligence Scale -Revised (WAIS-R; Wechsler, 1981), supporting the validity of the NART. The NART also probably gives a valid measure of premorbid IQ in most people with schizophrenia (Frith et al, 1991;Crawford et al, 1992).…”
Section: Simultaneous Estimate Of Premorbid and Current Intellectual mentioning
confidence: 77%
“…This is because a substantial proportion of people with established schizophrenia show no evidence of overall intellectual decline, especially in the early stages of the illness. Thus, more than half of a sample with first-episode schizophrenia showed no substantial IQ decline (Joyce et al, 2005), and in a sample with recently diagnosed schizophrenia (Johnstone et al, 2005), the mean values for premorbid and present IQ were almost identical, suggesting that most if not all individuals showed no substantial IQ decline. An additional limitation is that the NART may overestimate IQ decline in some people with schizophrenia and spuriously identify IQ decline in a small proportion of healthy people (Crawford et al, 1990;Russell et al, 2000).…”
Section: Simultaneous Estimate Of Premorbid and Current Intellectual mentioning
confidence: 99%
“…For Spatial Working Memory, the Executive Golf Task, a version of the Spatial Working Memory task (SWT) (Hutton et al, 1998;Joyce et al, 2005;Owen et al, 1996) was used that encompasses the distinction between maintenance and manipulation. This is a naturalistic version of the task with three dimensional graphics (Feigenbaum et al, 1996;Miotto et al, 1996), which has been used in schizophrenia (Kravariti et al, 2007;Toulopoulou et al, 2003Toulopoulou et al, , 2004.…”
Section: Working Memorymentioning
confidence: 99%
“…To study this issue, researchers have compared functioning in first episode and chronic schizophrenia across different domains. First episode schizophrenia shows executive dysfunction at this early stage, with some degree of clinical heterogeneity (Chan et al, 2006b;Joyce et al, 2005;Joyce & Roiser, 2007), but less impairment than is found in chronic schizophrenia (Chan et al, 2006a;Saykin et al, 1994). Profiles have varied between studies, with parallel flat profiles of diffuse general impairment, parallel nonflat profiles with selective impairments, and selective impairments specific to chronic schizophrenia (Albus et al, 1996;Blanchard & Neale, 1994;Chan et al, 2006a,b;Saykin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is not possible to evaluate the specific treatment effect that the programme had on a given cognitive function and, in particular, the specific role that each function may have played in improving schizophrenia patients' cognitive and social functioning. Second, some of these studies did not take into account the heterogeneity of cognitive deficits characterised in schizophrenia (e.g., Goldstein & Shemansky, 1995;Joyce, Hutton, Mutsatsa, & Barnes, 2005;Joyce & Roiser, 2007;Seaton, Goldstein, & Allan, 2001), as the same cognitive rehabilitation programme was administered to all the patients. For instance, in the case of working memory, two schizophrenia patients could show a completely different pattern of impairment, i.e., affecting differently the slave systems (phonological loop and visuospatial sketchpad) and/or the sub-processes of the central executive such as information manipulation, updating, and dual-task monitoring.…”
Section: Introductionmentioning
confidence: 99%